Pangindelan: Menelusuri Jejak Teknologi Canggih pada Sistem Penyaringan Air di Masa Kesultanan Banten sebagai Inovasi Berbasis Kearifan Lokal. - Untari, Aryanti Dwi (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2025)
This study examines Pangindelan, a traditional water filtration system from the Banten Sultanate, as both cultural heritage and a form of local technological innovation. Employing a descriptive-qualitative method with a historical research and technological ethnography approach, the study explores the function, construction, and contemporary relevance of Pangindelan. Findings reveal that the system utilized local materials such as sand, fibers, and terracotta to filter water from Lake Tasikardi before channeling it to Surosowan Palace. Beyond providing for domestic, agricultural, and ritual needs, Pangindelan reflects ecological wisdom, sociocultural values, and the spiritual dimension of Banten society. Its relevance to Sustainable Development Goal (SDG) 6 underscores its potential as an inspiration for developing affordable, environmentally friendly, and sustainable water purification technologies. Revitalization and further research are therefore essential to preserve this intangible cultural heritage while addressing global challenges of clean water scarcity.